Synthesis and characterization of mullite from Philippine kaolin clay deposit - Dejeto, Rodrigo V. (2006)
The Philippines has abundant deposits of kaolin clay minerals, which is the basic raw material for the production of traditional and advanced ceramics materials. The objective of this study is to synthesize mullite from Philippine kaolin clay and to characterize the physical and microstructural properties of the product. The local kaolin clay, sourced from Ilocos Norte, Philippines, known as Solsona White Clay (SWC) was beneficiated through elutriation methods following the Stoke?s Law. Other materials used as precursors were Baker analyzed aluminum oxide (Al2O3) powder reagent and siruma silica. The synthesis of mullite was based from the composition of theoretical mullite having 71.79% Al2O3 and 28.21% SiO2. The aluminum oxide was substituted with 0, 5, 10, 15, 20 and 50% SWC together with siruma silica, pressed and sintered then analyzed. The primary runs were made using a two level full factorial experiment as a screening procedure for the following process parameters: (a) % SWC substitution (b) sintering temperature and (c) sintering time. Results of the microstructural analysis of the control formulation sintered at 1150 degree celcius for 3 and 7 hours showed locally textured grainy structure, microcracks and pores at different orientations. There was an abrupt grain growth and amorphous or glassy structures at sintering temperature of 1400 degree celcius for 3 and 7 hours. However, for the samples with 5, 10 and 15% SWC substitutions showed formation of small islands of locally textured grainy structure, indicating the start of preferred grain alignment. Small crystals started to grow and the formations of column-like grains were also observed. The increased melting and nucleation of the fused grains was evident at 20% and 50% SWC substitutions. The formations of the melted structure that indicated melt penetration and liquid film were also observed at higher sintering temperatures and longer sintering time. The mullite and cristobalite phase transformations were evident at 1400 degree celcius sintering temperature. The EDX analysis verified the presence of Al, Si and O in sintered samples, which are the major components of mullite. The average volume shrinkage (11.63%) and apparent porosity (33.20%) of the sintered samples were within the prescribed standard range of <15% and 30-60% respectively, however the bulk density (2.06 g/cm3) was slightly higher than as prescribed (1.726 g/cm3). The final results were categorized under porous mullite.